Ang munting tindera ng posporo - Andersen, Hans Christian 1805-1875.; Langley, Glynis; Fryer, Davi (Manchester [England] World International Pub., 1980)
The wares of the poor little match girl illuminate her cold world, bringing some beauty to her brief, tragic life.
Keywords: Fairy tales